Fabricação e caracterização de cerâmicas multifuncionais à base de CaSr3Cu3-xTi4O12 para aplicações ópticas e eletro-eletrônicas - Orrego Gonzalez, Santiago [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Ceramics of CaCu3Ti4O12 (CCTO) areof scientific interest due to their multi functionality. In this work, ceramic powders of CaSrCu3-xTi4O12 with x=0,00, 0,15, 0,30, 1,50, 2,70 and 3,00 were prepared. These powders were thermally characterized by the thermogravimetry technique, was concluded the need use of two calcination temperatures, 950ºC for samples with low content of Sr2+ and 1050ºC for those with high content. To the sample in powder structural characterization was realized with the DRX technique that reveals the presence of pure phase of CCTO for x = 0,00, the sample of x = 0,15 present the phase of CCTO and the phase of CaTiO3, which ones are present too in the sample of x = 0,30 combined with the phase of (Sr0,75Ca0,25)TiO3(SCTO). The samples of x = 1,50 and 2,70 show the CCTO phase the SCTO phase and finally the sample of x = 3,00 show the pure phase of SCTO. Also was made a study by Raman spectroscopy techique indicates the presence of characteristic modes of the CCTO phase in all the samples, this because the SCTO phase also show this type of vibrational modes in the [TiO6] cluster. Finally the optical and photoluminescent properties were characterized, by the UV-vis technique was determined the energy gap values, the samples of x = 0,00, 0,15, 0,30 show gap values of 2,03, 2,28 and 2,35 eV respectively. Meanwhile each of the samples of x = 1,50 e 2,70 show two energy gaps, on at 2,12 and the other at the 3,16 eV; finally the sample of x = 3,00 present a unique energy gap of 3.33 eV. The photoluminescent property present an improvement compared with the pure phase of CCTO for samples with x = 2,70 and 3,00, this is probably due t the presence of oxygen vacancies in the [ToO6] clusters. To the other samples, this property was negatively affected by the substitution of Cu2+ by Sr2+. This characterizations were newly made by using a single calcination temperature, 1050ºC, reducing the number of variables that influence in the...

Cerâmicas à base de CaCu3Ti4O12 (CCTO) são de interesse científico e tecnológico devido a sua multifuncionalidade. Neste trabalho foram preparados pós cerâmicos por reação em estado sólido de CaSrxCu3-xTiO12 com x = 0,00; 0,15; 0,30; 1,50; 2,70 e 3,00. Os pós foram caracterizados termicamente utilizando a técnica da temperatura da termogravimetria, mediante esta técnica foi determinada à necessidade do uso de duas temperaturas de calcinação: 950ºC para amostras com baixo teor de Sr2+ e 1050ºC para as de maior teor. A técnica de difratometria de raios X (DRX) em nas amostras na forma de pó revelou a presença da fase pura de CCTO para x = 0,00; a amostra com x=0,15 apresentou a fase de CCTO e a fase CaTiO3 (CTO), as quais também estão presentes na amostra com x = 0,30 combnadas com a fase de (Sr0,75Ca0,25) TiO3 (SCTO). As amostras com x = 3,00 mostrou presença da fase pura de SCTO. A técnica de espectroscopia Raman indicou a presença dos modos de oscilação característicos da fase CCTO em todas as amostras, isto devido às fases CTO e SCTO também apresentarem cluster de [TiO6] na estrutura. As propriedades ópticas e fotoluminescentes dos pós cerâmicos foram analisados mediante a técnica de UV-vis onde foram determinados os valores de energia de gap, sendo que as amostras com x = 0,00; 0,15 e 0,30 apresentaram valores de gap de 2,03; 2,28 e 2,35 eV, respectivamente. As amostras com x=1,50 e 2,70 apresentaram cada uma dois gaps de energia, um aos 2,12 e o outro aos 3,16 eV; a amostra de x=3,00 apresentou um único gap de 3,33 eV. A intensidade fotoluminescente apresentou uma melhora em relação a intensidade da fase pura de CCTO para as amostras com x = 2,70 e 3,00, isto devido provavelmente à presença de vacância e oxigênio geradas nos clusters de [TiO6]. Para as outras amostras a intensidade foi afetada negativamente pela substituição do Cu2+ pelo Sr2+. Estas caracterizações foram novamente realizadas...
Keywords: Fotoluminescencia; Material cerâmico; Termogravimetria; Raios X - Difração; Photoluminescence